2013
DOI: 10.1016/j.jcrs.2012.12.039
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of cannulas for ophthalmic surgery after cleaning and sterilization: Evaluation of the use of enzymatic detergent to remove residual ophthalmic viscosurgical device material

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 9 publications
0
7
0
6
Order By: Relevance
“…For the American Society of Cataract and Refractive Surgery and the American Society of Ophthalmic Registered Nurses (10) , when not specified by the manufacturer, ophthalmological instrumentation must be rinsed with deionized or sterile distilled water. This observation is supported by a study that demonstrated the absence of cytotoxicity in cannula processed and rinsed with sterile distilled water (5) . In the present study, the sterility of distilled water did not prove to be an essential condition for the absence of cytotoxicity, as the mean cell viability was 91%.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…For the American Society of Cataract and Refractive Surgery and the American Society of Ophthalmic Registered Nurses (10) , when not specified by the manufacturer, ophthalmological instrumentation must be rinsed with deionized or sterile distilled water. This observation is supported by a study that demonstrated the absence of cytotoxicity in cannula processed and rinsed with sterile distilled water (5) . In the present study, the sterility of distilled water did not prove to be an essential condition for the absence of cytotoxicity, as the mean cell viability was 91%.…”
Section: Discussionmentioning
confidence: 65%
“…For example: by using predetermined volumes, and establishing how long technological apparatuses are used, such as high-pressure water jet pistol. Vague and subjective recommendations, such as rinse abundantly with no further details can limit the transposition of the results to the assistance as well as not observing any additional cleaning instructions provided by the manufacturer (5) . In the comparative control group with no drying, none of the samples presented cytotoxicity, suggesting that drying may not influence cytotoxicity, at least not for the period of an hour and a half between the end of the sample cleaning and the beginning of sample drying.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reconhecidamente a limpeza é o processo fundamental para a garantia da segurança dos produtos para saúde (Alfa et al, 1996, Graziano, 2003; pois remove resíduos químicos, sangue, proteínas, substâncias orgânicas, além de reduzir o número de microrganismos (Ribeiro, 2010 (Tamashiro et al, 2013).…”
Section: Resultsunclassified
“…após a contaminação desafio (Tamashiro et al, 2013 (Fonseca, 1997). Este estudo demonstra a importância do monitoramento e do controle da qualidade da água no CME, conforme estabelecido na RDC ANVISA n. 15 de 2012 (Brasil, 2012), incluindo a água para geração do vapor na autoclave.…”
Section: Resultsunclassified